Bi2Te3-Sb2Te3 on polymeric substrate for X-ray detectors based on the seebeck effect - Rocha, J. G. (2012)
A theoretical and experimental basis for a x-ray detector concept, based on the conversion of x-rays into thermal energy is presented. The detector follows an indirect approach: the x-rays are first converted into thermal energy, which is then converted into electrical signals by the Seebeck effect. The detector does not need high operating voltages as the detectors based on photoconductors, it shows higher efficiency in energy conversion than x-ray detectors based on scintillators and it has a better intrinsic signal to noise ratio than both photoconductor and scintillator methods. Moreover, this technique allows the fabrication of x-ray detectors on polymeric substrates, which is not so viable with the other aforementioned methods. As a drawback, the frequency response of this detector is usually low. This drawback can be overcome by reducing the mass of the detector.